Social status and public expectations: Self-selection of high-skilled migrants - Christian Lumpe; Claudia Lumpe; Jürgen Meckl (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
We analyze public expectations about migrants' provision of work effort as a driving force in the self-selection process of high-skilled migrants. We adopt and extend Piketty's (1998) theoretical framework of social status and work out how country-specific public expectations affect the migrants' choice about their country of destination. As a result, we relate Germany's attested low attractiveness for high-skilled immigrants to its society's attitudes towards immigrants. We develop measures to increase Germany's attractiveness in the competition about talents. – – Wir analysieren Erwartungen der Öffentlichkeit im Einwanderungsland an den Arbeitseinsatz von Immigranten als treibende Kraft für die Selbstselektion hochqualifizierter Immigranten. Dazu übernehmen und erweitern wir das theoretische Modell zum sozialen Status von Piketty (1998) und zeigen, dass länderspezifische öffentliche Erwartungen die Entscheidung von Immigranten, in welches Land sie migrieren, beeinflussen. Im Ergebnis verknüpfen wir Deutschlands attestierte geringe Attraktivität für hochqualifizierte Immigranten mit der Einstellung der Öffentlichkeit gegenüber Immigranten. Wir zeigen Maßnahmen auf, anhand derer Deutschland seine Attraktivität im internationalen Wettbewerb um Talente steigern kann.
Keywords: F22; 330; immigration; social status